Fetal sex and maternal pregnancy outcomes: a systematic review and meta-analysis - Broere-Brown, Zoe A. (Biol Sex Differ, 2020)
BACKGROUND: Since the placenta also has a sex, fetal sex–specific differences in the occurrence of placenta-mediated complications could exist. OBJECTIVE: To determine the association of fetal sex with multiple maternal pregnancy complications. SEARCH STRATEGY: Six electronic databases Ovid MEDLINE, EMBASE, Cochrane Central, Web-of-Science, PubMed, and Google Scholar were systematically searched to identify eligible studies. Reference lists of the included studies and contact with experts were also used for identification of studies. SELECTION CRITERIA: Observational studies that assessed fetal sex and the presence of maternal pregnancy complications within singleton pregnancies. DATA COLLECTION AND ANALYSES: Data were extracted by 2 independent reviewers using a predesigned data collection form. MAIN RESULTS: From 6522 original references, 74 studies were selected, including over 12,5 million women. Male fetal sex was associated with term pre-eclampsia (pooled OR 1.07 [95%CI 1.06 to 1.09]) and gestational diabetes (pooled OR 1.04 [1.02 to 1.07]). All other pregnancy complications (i.e., gestational hypertension, total pre-eclampsia, eclampsia, placental abruption, and post-partum hemorrhage) tended to be associated with male fetal sex, except for preterm pre-eclampsia, which was more associated with female fetal sex. Overall quality of the included studies was good. Between-study heterogeneity was high due to differences in study population and outcome definition. CONCLUSION: This meta-analysis suggests that the occurrence of pregnancy complications differ according to fetal sex with a higher cardiovascular and metabolic load for the mother in the presence of a male fetus. FUNDING: None.